2016
DOI: 10.7603/s40730-016-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Significance of mast cells in non-neoplastic and neoplastic lesions of uterine cervix

Abstract: Abstract-Background:Mast cells are involved in multiple biological events. The significance of mast cells in non-neoplastic and neoplastic lesions of the cervix has been studied with conflicting results. Its presence in a tumor has been described as evidence of host immunologic antitumor response, angiogenesis and tumor invasion. Aims/Objectives: To study mast cell density in various cervical lesions using Toluidine blue stain. To compare the sections studied with conventional Toluidine blue staining and Tolui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Mast cells clustered in C3, on the other hand, were previously shown to progressively increase along the continuum from CIN1 to SCC (40). However, another study with fewer samples reported the least mast cell count in SCC compared to SILs and normal cervix (42), which is in line with our results. The role of mast cells in HPV lesions is uncertain.…”
Section: Discussionsupporting
confidence: 92%
“…Mast cells clustered in C3, on the other hand, were previously shown to progressively increase along the continuum from CIN1 to SCC (40). However, another study with fewer samples reported the least mast cell count in SCC compared to SILs and normal cervix (42), which is in line with our results. The role of mast cells in HPV lesions is uncertain.…”
Section: Discussionsupporting
confidence: 92%
“…Mast cells play a critical role in the TIME of many cancers and their effect on promoting or inhibiting tumors depends on the type and stage of cancer [185,186]. Mast cells (tryptase-positive and tryptase/chymase-positive) are also found in the normal human cervix, and their number increases in benign inflammatory conditions [187][188][189]. A recent study reported a widespread distribution of mast cells in CC tissues and patients with low mast-cell density in their TIME had better overall survival rates [190].…”
Section: Mast Cells In the CC Timementioning
confidence: 99%
“…It has been observed that the number of mast cells increases in proportion to the cervical lesion grade [131]. There are other groups, however, that have not found the same correlation, concluding that mast cells may display an important role in inflammatory lesions but not neoplastic lesions [132]. Whether the inflammatory response can be part of the carcinogenic process initiated by HPV it is a frequent and much-discussed topic that still needs to be addressed.…”
Section: Hpv and The Microenvironmentmentioning
confidence: 99%